2020
DOI: 10.1021/acsearthspacechem.0c00035
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Particles and Aquatic Colloids on the Oxidation of Sb(III) in Natural Water

Abstract: Antimony (Sb) is a hazardous metalloid that is ubiquitous in the environment. Its toxicity and mobility are strongly influenced by the valence state. Particles and aquatic colloids are abundant in natural water; however, there is little understanding of how Sb­(III) is oxidized by these substances. In this study, cross-flow ultrafiltration is used to separate the substances in natural water samples into macroparticles (>1 μm), microparticles (1–0.1 μm), colloids (<0.1 μm, >1 kDa), and dissolved substances (<1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…61 Sb(III) oxidation solely by O 2 is slow, 62 but active substances such as Fe(III)-NOM can accelerate Sb(III) oxidation. 63 In this study, SAWC oxidised Sb(III) to the more mobile Sb(V) in all solutions tested, which explains the generally low removal of Sb(III) (2.3 < log K d < 3.3). The BC related oxidation of Sb is illustrated in Fig.…”
Section: Oxidation To Sb(v) Limits Sb(iii) Removal By Sawcmentioning
confidence: 62%
“…61 Sb(III) oxidation solely by O 2 is slow, 62 but active substances such as Fe(III)-NOM can accelerate Sb(III) oxidation. 63 In this study, SAWC oxidised Sb(III) to the more mobile Sb(V) in all solutions tested, which explains the generally low removal of Sb(III) (2.3 < log K d < 3.3). The BC related oxidation of Sb is illustrated in Fig.…”
Section: Oxidation To Sb(v) Limits Sb(iii) Removal By Sawcmentioning
confidence: 62%
“…Therefore, it is expected that Fe–OM colloids, which are ubiquitous in subsurface environments, play a crucial component in Sb mobility in natural environments. 25…”
Section: Introductionmentioning
confidence: 99%
“…24 Sb can usually form associations with low-molecular-weight ligands and interact with Fe-OM colloids in aquatic environments. 1,25 For example, low Fe(II) and high HA concentrations suppressed the formation of thermodynamically more stable goethite and hematite, which benefit the formation of substantial amounts of Fe(III)-OM colloids that affect the mobility and speciation of Sb under OM-rich conditions. 26 This is also evidenced by Hockmann et al, 27 who observed that >15% of Sb(V) occurred in the colloidal phase at a molar Fe/Sb ratio of 400.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation